2003
DOI: 10.1021/jp0265900
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Ultrafast Excited State Proton Transfer in Anionic Micelles

Abstract: Fast excited state proton transfer reactions at the surface of anionic sodium dodecyl sulfate (SDS) micelles have been investigated using the photoacid 4-methyl-7-hydroxyflavylium (HMF) chloride as probe. The acidbase kinetics of excited HMF are straightforward in water, with biexponential fluorescence decays reflecting ultrafast deprotonation of the excited acid (AH + )* (k d ) 1.5 × 10 11 s -1 or ca. 6 ps) and diffusion-controlled protonation of the excited base A* (k p ) 2.3 × 10 10 L mol -1 s -1 at 20°C). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(144 citation statements)
references
References 12 publications
6
137
0
1
Order By: Relevance
“…Fluorescence lifetimes were also obtained in solution and in the solid state and initial studies (with time-resolution of ≈150 ps) suggested single-exponential decays for all compounds (see Table 2). However, when the solution decays are investigated with picosecond time resolution (∼3 ps) 11 the decays are now multiexponential (bi-and triexponential) following decay laws according to eq 5; where a i (i ) 1, 2, for BPH and BPHF and i ) 1, 2, 3 for BTF) are the pre-exponential factors and τ j are the decays times with j ) 2 for BPH and BPHF and j ) 3 for BTF. It can be seen from Figure 2 that for BPHF and BTF the shortest decay time appears as a rise time.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence lifetimes were also obtained in solution and in the solid state and initial studies (with time-resolution of ≈150 ps) suggested single-exponential decays for all compounds (see Table 2). However, when the solution decays are investigated with picosecond time resolution (∼3 ps) 11 the decays are now multiexponential (bi-and triexponential) following decay laws according to eq 5; where a i (i ) 1, 2, for BPH and BPHF and i ) 1, 2, 3 for BTF) are the pre-exponential factors and τ j are the decays times with j ) 2 for BPH and BPHF and j ) 3 for BTF. It can be seen from Figure 2 that for BPHF and BTF the shortest decay time appears as a rise time.…”
Section: Resultsmentioning
confidence: 99%
“…3 ps. [21] Molecular Orbital Calculations: Molecular orbital calculations were carried out using HyperChem 5.0 program. [22] Molecular geometries were optimized using PM3 and single point calculations were performed using PM3-CI, AM1-CI and ZINDO/S-CI.…”
Section: Methodsmentioning
confidence: 99%
“…Time-resolved Fluorescence Spectroscopy-Fluorescence decays were measured using a time-correlated single-photon-counting apparatus (20). Vertically polarized excitation light at 292 nm was obtained with the third harmonic of the output (876 nm) of a mode-locked Ti-sapphire laser (Spectra-Physics Tsunami) pumped by a Millenia X (SpectraPhysics) laser.…”
Section: Methodsmentioning
confidence: 99%